Load to Failure and Stiffness: Anchor Placement and Suture Pattern Effects on Load to Failure in Rotator Cuff Repairs. Issue 4 (7th April 2015) - Esquivel, Amanda O.; Duncan, Douglas D.; Dobrasevic, Nikola; Marsh, Stephanie M.; Lemos, Stephen E.
Background: Rotator cuff tendinopathy is a frequent cause of shoulder pain that can lead to decreased strength and range of motion. Failures after using the single-row technique of rotator cuff repair have led to the development of the double-row technique, which is said to allow for more anatomical restoration of the footprint. Purpose: To compare 5 different types of suture patterns while maintaining equality in number of anchors. The hypothesis was that the Mason-Allen–crossed cruciform transosseous-equivalent technique is superior to other suture configurations while maintaining equality in suture limbs and anchors. Study Design: Controlled laboratory study. Methods: A total of 25 fresh-frozen cadaveric shoulders were randomized into 5 suture configuration groups: single-row repair with simple stitch technique; single-row repair with modified Mason-Allen technique; double-row Mason-Allen technique; double-row cross-bridge technique; and double-row suture bridge technique. Load and displacement were recorded at 100 Hz until failure. Stiffness and bone mineral density were also measured. Results: There was no significant difference in peak load at failure, stiffness, maximum displacement at failure, or mean bone mineral density among the 5 suture configuration groups ( P < .05). Conclusion: According to study results, when choosing a repair technique, other factors such as number of sutures in the repair should be considered to judge the strength of the repair. Clinical Relevance: Previous in vitro studies have shown the double-row rotator cuff repair to be superior to the single-row repair; however, clinical research does not necessarily support this. This study found no difference when comparing 5 different repair methods, supporting research that suggests the number of sutures and not the pattern can affect biomechanical properties.